Dewey's dream : universities and democracies in an age of education reform : civil society, public schools, and democratic citizenship - Benson, Lee; Harkavy, Ira Richard; Puckett, John L., 1947- (Temple University Press, 2007)
This timely, persuasive, and hopeful book reexamines John Dewey's idea of schools, specifically community schools, as the best places to grow a democratic society that is based on racial, social, and economic justice. The authors assert that American colleges and universities bear a responsibility for-and would benefit substantially from-working with schools to develop democratic schools and communities. Dewey's Dream opens with a reappraisal of Dewey's philosophy and an argument for its continued relevance today. The authors-all well-known in education circles-use illust.